2017
DOI: 10.1155/2017/9075878
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene Carbon Nanotubes Nanocomposites: Combined Influence of Block Copolymer Compatibilizer and Melt Annealing on Electrical Properties

Abstract: We study the influence of melt annealing and the presence of a block copolymer compatibilizer on the electrical properties of polypropylene carbon nanotubes (CNT) nanocomposites from the DC limit to microwave frequencies and link it to the morphological details. We show that the compatibilizer concentration controls three types of morphologies: separate CNT agglomerates, a network of well dispersed but interconnected CNT, and individualized but separate nanotubes. This explains why conductivity reaches an opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…MWCNTs polymer composites offer a large flexibility for design and control of microwave absorption behaviors, as the composites can be tailored through changes in loading fractions, matrix materials, complex permittivity, and loss tangent of MWCNTs polymer composites. Many microwave studies have been reported with CNTs polymer composites with high (i.e., greater than 2.0 wt%) and low loadings of MWCNTs in the matrix. Although these composites are found to show good microwave absorbing performances with reflection loss (RL) of more than 90%, the absorbing frequency band is very narrow in most of the cases (∼2–3 GHz).…”
Section: Mwcnts Polymer Nanocomposites As Rammentioning
confidence: 99%
See 1 more Smart Citation
“…MWCNTs polymer composites offer a large flexibility for design and control of microwave absorption behaviors, as the composites can be tailored through changes in loading fractions, matrix materials, complex permittivity, and loss tangent of MWCNTs polymer composites. Many microwave studies have been reported with CNTs polymer composites with high (i.e., greater than 2.0 wt%) and low loadings of MWCNTs in the matrix. Although these composites are found to show good microwave absorbing performances with reflection loss (RL) of more than 90%, the absorbing frequency band is very narrow in most of the cases (∼2–3 GHz).…”
Section: Mwcnts Polymer Nanocomposites As Rammentioning
confidence: 99%
“…Depending on the nature of the filler, the weight percentage used, and the method of preparation, significant differences in the composite properties may be obtained. More recently, particular nanocarbon‐based reinforced composites have been proposed to improve performances of traditional materials while reducing the overall multilayer thickness. Till now, carbon nanotubes (CNTs) reinforced polymer composites are most extensively studied materials for radar absorbing applications, in comparison with traditional engineering materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, an additional step for chemical modification is typically necessary. Alternatively, as reported by several groups, block copolymers might serve as efficient compatibilizers between fillers and polymer matrices [40,41]. As such, this research introduces the innovative idea to compatibilize fixed carriers in polymer matrices using suitable block copolymers.…”
Section: Introductionmentioning
confidence: 88%
“…Ultrathin sections of approximately 70-100 nm in thickness were cut using a cryodiamond knife (Diatome, Switzerland) and collected on 400 mesh copper grids. The whole procedure is very similar to that described in [23]. www.videleaf.com…”
Section: Characterization Toolsmentioning
confidence: 94%